SYNERGISING GREEN ACCOUNTING AND TECHNOFINANCE FOR BUSINESS PERFORMANCE: THE MODERATING ROLE OF ISLAMIC VALUES - Alpiansah, Restu; Fitriyah, Nur; Anggriani, Rini; Lewandowski, Mariusz; Kopcewicz, Katarzyna Liczmańska (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This research examines the synergistic impact of Green Accounting and Technofinance on Business Performance, with Islamic Values serving as a moderating variable, within the framework of small and medium-sized enterprises (SMEs) in West Nusa Tenggara, Indonesia. Data were acquired from 180 SME owners using a purposive sampling strategy, all of whom had halal certification and engage in Islamic-based entrepreneurship. The study model was evaluated utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) with 36 measurement items derived from a four-point Likert scale. The findings indicate that both Green Accounting and Technofinance substantially improve Business Performance, underscoring the significance of environmental accountability and financial digitization in augmenting profitability, efficiency, and sustainability. Nonetheless, Islamic values did not substantially influence these linkages, indicating that ethical and religious principles function more as a normative basis than as an empirical enhancer of the observed correlations. These findings enhance the literature by amalgamating environmental, financial technology, and religious views in the analysis of business performance, providing theoretical backing from stakeholder theory and the resource-based view. The findings suggest that SME managers ought to prioritize environmental reporting systems and the integration of financial technology to maintain competitiveness, while adhering to Islamic ethical values as foundational principles. The study's limitations include its regional scope and sample size; therefore, future research should expand geographical coverage, enhance sample diversity, and integrate additional variables such as innovation capability and market orientation to improve generalizability and yield deeper insights into sustainable performance.